The Dispute Concerning Rhetoric in Hellenistic Thought - Liebersohn, Yosef Z. (Hypomnemata, 2010)
This study tries to reconstruct the dispute over rhetoric in Hellenistic thought, by using two main interrelated axes. Firstly, it delineates the exact milieu in which this dispute took place, including locations, dates and persons. Secondly, five main arguments used against rhetoric have been reconstructed, all of which concentrate on rhetoric's claim to be considered an art.